A New Species Of Gongylosoma (Squamata: Colubridae) From Pulau Tioman, West Malaysia - Das, Indraneil; Grismer, L. Lee; Tzi, Ming Leong (The Herpetologists’ League, Inc., 2003)
A new species of Gongylosoma is described from Pulau Tioman, a small island 38 km off the southeast coast of Pahang, West Malaysia, in the South China Sea. This species differs from all other Gongylosoma in having a single, enlarged, posterior temporal; chinshields of equal size; and a thin nuchal band that contacts a vestigial vertebral stripe. The new species forms a clade with G. nicobariense from the Nicobar Islands and G. longicauda from Borneo, Java, and Sumatra and is the sister species of the latter.